Education On Consuming Food With Balanced Nutrition In Creating Superior Resources In The Village - Lubis, Mitra Musika; Yuliati, Luluk; Asrijal, Andi; Utami, Cahyaning Rini; Gunawan, Untung; Putri, Elvina Triana (Universitas Pahlawan Tuanku Tambusai, 2024)
This community service was carried out in a number of villages, namely Sukaramai Satu Medan Area village, Wonosari Gempol village, and Gerit Pati village for 40 days by finding problems and solutions as follows. During the forty days of the field service, the service providers implemented vegetable and fruit standards as recommended by the Ministry of Health. The service providers not only socialized the village community theoretically, but also directly provided practices according to the financial capabilities of the service providers. Thus, the service providers believe that education on food consumption with balanced nutrition can create superior human resources in the village.